ANALISIS PENGARUH TRUST, APPLICATION QUALITY, PERCEIVED USEFULNESS TERHADAP INTENTION TO PURCHASE DAN ACTUAL SYSTEM USE (STUDI KASUS PADA APLIKASI KAI ACCESS) - Ahmad Rifaldi; Bintoro Tri Wicaksono; Dixsy Faturochman Putra (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study is to determine the effect of trust, application quality, and perceived usefulness on the intention to purchase and actual system use of the KAI ACCESS application between the ages of 19 -39 years in Jabodetabek. From the 204 respondents obtained, data analysis was then carried out and the results showed that the trust variable did not have a significant effect on the intention to purchase, while the application quality and perceived usefulness variables had a significant influence on the intention to purchase variable, then the intention to purchase variable also had a significant effect. significant to the actual system use variable. From the analysis of the coefficient of determination, it is found that the variables of trust, application quality and perceived usefulness can explain the variable intention to purchase by 81.1%, while the remaining 18.9% is explained by other variables and the variable intention to purchase can explain the actual system use variable of 52 .5% and the remaining 47.5% is explained by other variables.